Aerodynamics investigation of MAV with flexible wing - Zeng, Zibin (2011)
This report describes research performed on various configurations of a flexible-wing Micro Air Vehicle (MAV). Flexible-wing MAV’s advantage over rigid-wing MAV is that it is able to fly much smoother in gusty wind conditions. As such, wind tunnel experiments at free stream velocity of 21 m/s were carried out on various flexible wing configurations to determine ways of further enhancing their lift and longitudinal stability by means of varying the degree of wing flexibility. Wing flexibility was first varied in terms of the wing frame’s number and orientation of battens. Thereafter, using the best wing frame configuration, wing flexibility was varied in terms of skin material and the amount of initial extension or slack applied to the skin during fabrication. Experimental results showed that the wing frame without battens and elastic latex skin without initial extension or slack exhibited the best overall lift and longitudinal stability. However, this flexible wing configuration had also exhibited significantly higher drag than the rigid wing. Forced pitching oscillation tests were also carried out on the said flexible wing configuration to determine its longitudinal dynamic stability. However the results were inconclusive and no trends can be observed for the pitch rate derivatives of pitching moment coefficients. Finally, tests were carried out on the said flexible wing with a propeller-based propulsion system on its trailing edge to determine the propeller effects. Results showed that the propeller effects slightly destabilise the flexible wing. To conclude, the high drag values slightly degraded the flexible wing’s level flight performance but the high lift values increased the performance of instantaneous manoeuvres.